Embedded system design of a maximum power point tracking controller for traffic light system powered by photovoltaic - Muhida, Riza; Djajadi, Arko; Mohamad, Nor Hilmi; Legowo, Ari (UNSYS Digital, 2015)
Photovoltaic traffic light system is a significant application of renewable energy source. The develop the system use solar energy as an alternative effort of local authority to reduce expenditure for paying fees to power supplier which the power comes from conventional energy source. Since photovoltaic modules still have relatively low conversion efficiency, an alternative control of maximum power point tracking (MPPT) method applied to the traffic light system. MPPT is intended to catch up the maximum power at daytime in order to charge the battery at the maximum rate in which the power from the battery is intended to be used at night time or cloudy day. MPPT is actually a DC-DC converter that can step up or down of voltage in order to achieve the maximum power using Pulse Width Modulation (PWM) control. Based on experiment, we obtained the used MPPT voltage of operation at 16.454 V, this value had error 2.6% compared with maximum power point voltage of PV module which is 16.9V. Based on this result the MPPT control work was successfully deliver the power from PV module to battery maximally.